Corporate Restructuring through Mergers: A Case of ICICI Bank - Wajid, Abdul; Singh, Harjit; Ansari, Abdul Aziz (Indian Journal of Finance, 2019)
In the time of financial turbulence, corporate restructuring through mergers is one of the most prominent business strategies for corporates to achieve more significant market share, enhance profitability, expand its reach into the new markets, and also to obtain economies of scale. The objective of this study was to examine the impact of mergers on the short run market performance and long-run operating performance of ICICI Bank, one of the leading private sector banks in India. The present study distinguished itself from others by analyzing three essential measures simultaneously: (a) short run abnormal returns to shareholders, (b) long term operating performance of acquirer, and (c) strategic similarity analysis. Event study methodology, ratio analysis, and strategic similarity analysis were applied to study the short term and long-term performance of ICICI Bank. The findings revealed that the shareholders of ICICI Bank did not respond positively surrounding the announcement of its merger. However, the post-merger financial performance of ICICI Bank improved as was evident in its post-merger ratios and strategic similarity analysis. The Indian banking industry has witnessed a surge in consolidation activities through mergers and acquisitions. This study is rational in today's changing banking business environment to understand the value creation aspects of corporate restructuring moves primarily through mergers.